2005
DOI: 10.1097/00003072-200502000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Contradictory Supranormal Function in Hydronephrotic Kidneys: Fact or Artifact on Pediatric MAG-3 Renal Scans?

Abstract: SRF in unilateral hydronephrosis is, at least, in part, technical in origin in this particular pediatric patient population with tubular immaturity (ie, physiological high background activity) and asymmetric kidney size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 12 publications
3
22
1
Order By: Relevance
“…Inanir et al suggest that a higher DRF reported in larger hydronephrotic kidneys is related to higher intrarenal vascular background activity. They determined that these kidneys had a higher renal area ratio (number of pixels within the ROI of the hydronephrotic kidney divided by that of the normal contralateral kidney) [5]. Our results are concordant with the suggestion that when DRF calculations were corrected according to the kidney area, by dividing the total counts to the number of pixels in the kidney's ROI, there was a clinically meaningful decrease in DRF of kidneys with a high hydronephrosis grade.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Inanir et al suggest that a higher DRF reported in larger hydronephrotic kidneys is related to higher intrarenal vascular background activity. They determined that these kidneys had a higher renal area ratio (number of pixels within the ROI of the hydronephrotic kidney divided by that of the normal contralateral kidney) [5]. Our results are concordant with the suggestion that when DRF calculations were corrected according to the kidney area, by dividing the total counts to the number of pixels in the kidney's ROI, there was a clinically meaningful decrease in DRF of kidneys with a high hydronephrosis grade.…”
Section: Resultssupporting
confidence: 88%
“…When we examined this discordant data, common parameters emerged, including higher hydronephrosis grade and larger APD (cases with supranormal function and cases categorized as 40-45 or \40 % are marked in In MAG-3 diuretic renography's one of the aspects is calculation of the DRF and the second is assessment of drainage. Inanir et al suggest that the preferred radiopharmaceutical for DRF estimation in unilateral hydronephrosis should be DMSA [5]. Despite the fact that DMSA studies require minimal background corrections, the chosen technique might still be unsatisfactory in some cases [6].…”
Section: Resultsmentioning
confidence: 99%
“…In spite of these observations between the MAG-3 and DMSA RRF estimations [4,5], some problems also exist in children with unilateral hydronephrosis, such as supranormal RRF estimations and methodological considerations [3,6]. In our study, a disagreement was revealed only in a limited number of cases with a difference of C5% between RRF estimations or supranormal functions (Tables 1, 4).…”
Section: Discussioncontrasting
confidence: 53%
“…The prevalence of supranormal function in our present series was 11.5%, which was consistent with previous reports [1,[8][9][10][11]19,20]. Some authors considered supranormal function as a technical artefact related to the use of different radiotracers, the timing after radionuclide administration to accurately estimate split renal function, the identification of areas of interest, the calculation method or the subtraction of background activity [8,14,[21][22][23]. Pippi Salle et al [12] experimentally demonstrated that supranormal function is not an artefact but a physical phenomenon based on parenchymal thinning related to significant hydronephrosis and radioisotope distribution relative to the c-camera [12].…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of supranormal function in our present series was 11.5%, which was consistent with previous reports . Some authors considered supranormal function as a technical artefact related to the use of different radiotracers, the timing after radionuclide administration to accurately estimate split renal function, the identification of areas of interest, the calculation method or the subtraction of background activity . Pippi Salle et al.…”
Section: Discussionsupporting
confidence: 92%